Doping Education And The Dangers As A Prevention To Use It In The Pabbsi Athlet Of Padang City - hilmainur - syampurma; rika sepriani (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
Doping is the use of materials or physiological substance in large quantities that are entered in to the body in an unnatural way, with the spesific purpose of achhieving artificial capability improvement in a match. The use of doping every year continues to increase, especially in Indonesia. PABBSI is an organization that houses athletes in the branches of weight lifting and body building in Indonesia. For the sake of getting a victory, many athletes are willing to do anything including the use of drugs that are prohibited before the match with the aim of improving perfomance appearance. Socialization and education on the use of doping in Indonesia, especially in Padang is still lacking so that many athletes dont know and understand the use of doping and it’s dangers to their physiology system and the impact on their future carier. The lack of information from related parties is felt as a major factor in the high use of doping among athletes. For this reason, the team want to carried out to provide update information on the use of doping and provide education on a dangers of using doping for athletes, especially in Padang so as to prevent their use.